2005
DOI: 10.1016/j.jacc.2004.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive diagnosis of coronary artery disease in patients with heart failure and systolic dysfunction of uncertain etiology, using late gadolinium-enhanced cardiovascular magnetic resonance

Abstract: In patients with HF and LV systolic dysfunction without clinical suspicion of CAD, LGE-CMR is an excellent tool for classifying patients in relation to the presence or absence of underlying CAD. Thus, CMR might offer a valid alternative to coronary angiography for the detection of CAD in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 41 publications
4
73
1
1
Order By: Relevance
“…The absence of LGE in patients with severe coronary disease is an important finding. Previous publications predict that, in the absence of ischemic type scar on LGE-CMR, patients are unlikely to have significant coronary ischemia [16,17]. The present data suggest that absence of LGE does not equate to the absence of ischemia or significant coronary artery disease.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The absence of LGE in patients with severe coronary disease is an important finding. Previous publications predict that, in the absence of ischemic type scar on LGE-CMR, patients are unlikely to have significant coronary ischemia [16,17]. The present data suggest that absence of LGE does not equate to the absence of ischemia or significant coronary artery disease.…”
Section: Discussioncontrasting
confidence: 45%
“…The existence of patients with coronary disease and no LGE has been reported in previous studies. Soriano et al reported five patients with CAD but no enhancement, however, they had ''stenosis in nonproximal segments of the right coronary or left circumflex artery [which] would not explain the severity of the LV dysfunction'' [17]. McCrohen iCA invasive angiography, PPV positive predictive value, NPV negative predictive value, CCTA dual source coronary computed angiography, CMR-LGE cardiac magnetic resonance with late gadolinium enhancement imaging et al [16] reported that mid-wall enhancement was present in 28% of patients with DCM, but in no patients with ischemic LV dysfunction, leading to the common perception amongst the clinicians that mid-wall enhancement does not equate to an ischemic etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have documented a significant positive correlation between the extent of subendocardial DCE and coronary stenoses, making this technique an excellent indicator of underlying significant CAD [18]. This has been reported also in patients without a clinical history of MI, but with angiographically documented coronary disease [19].…”
Section: Schlüsselwörtermentioning
confidence: 63%
“…In the absence of this pattern, a cardiomyopathy is the more likely diagnosis. Using this simple algorithm, CMR has established a role in differentiating ischaemic from non-ischaemic cardiomyopathies and should be considered in the evaluation of the etiology of heart failure patients [13][14][15].…”
mentioning
confidence: 99%